50. Optimizing Conferencing Freeware - Baggaley, Jon; Klaas, Jim; Wark, Norine; Depow, Jim (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
The increasing range of options provided by two popular conferencing freeware products, Yahoo Messenger and MSN Messenger, are discussed. Each tool contains features designed primarily for entertainment purposes, which can be customized for use in online education. This report provides suggestions for optimizing the educational potential of the two products: e.g., generating automated statements for conference moderators to use in controlling conference sessions, and for all participants to use in overcoming the high-bandwidth obstacle of online video transmission.